Escola “sem” Partido: a pseudo-neutralidade e o viés ultraconservador do movimento - Silveira, Danielli Maria Neves da (2019)
This dissertation is the result of investigations into the emergence, propagation and intentionalities of the movement "School without" Party, realized with the aim of understanding the movement and what it escapes, in the middle of a discourse that defends a supposed neutrality in school education. The movement emerges in the year 2004, however, it spreads more intensely after 2014, when it is transformed into a Bill, at a political moment conducive to the ultraconservative discourse in the field of politics and social values. Initially we try to present it from its emergence, analyzing it within the historical context, problematizing some contradictory questions at its core. In the sequence, we make an analysis, based on recent productions on the subject, that raise questions and intentionalities that do not appear immediately in the documents and discourses of the ESP, but that, when analyzed in depth, appear at its core. In the second and last chapter, we contrast the "neutrality" advocated by the "without" Party School. To do this, we turn to the classics of sociology: Emile Durkheim, Max Weber and Karl Marx. It is a bibliographical and documentary research of investigative and exploratory nature, based on the criticism of the movement "without" Party, which expresses the interests of the ruling class and spreads through a discourse of an ultraconservative nature. In order to do so, we used discussions carried out by researchers that deal with the contradictions in the content and in the form of what is proposed by ESP.